Comparison Of Starch Content And Transcriptomes Of Felled Oil Palm Trunks At 0 And 15 Days Of Storage - Hasri, Nur Hanis Alisa Md (2024)
The oil palm trees are logged for replantation after they reach their maximum productivity of palm oil production. Massive biomass waste such as the oil palm trunk (opt) is generated during the replanting process. The opt biomass residues have been reported to contain a high amount of starch and sugar (glucose, sucrose, and fructose) that have high potential for various industrial uses (e.G., in value-added products). However, low starch opts with no use and practicality have also been identified in the oil palm plantations. In this study, high-starch and low-starch opt were firstly felled and further stored for 15 days. A storage period of 15 days was used as 15 days is a sufficient period to transport the opts from the plantation and to deliver to industrial companies for further applications. More specifically, the top and middle parts of the trunks containing sugar and starch, on the day the trees were felled (day 0 of storage) and 15 days later (day 15 of storage) were examined. Within the storage period, the starch and sugar contents were identified and the transcriptomes of the felled opt were sequenced to distinguish the high and low-starch opt. During the 15 days of storage, the starch content slightly decreased while the sugar content slightly increased in all the opts.